The Blessings Behind the Covid-19 Outbreak: The Sustainability of MSMEs for Organic Products - Sri Muljaningsih; Firman Rosjadi Djoemadi; Dien Amalina Nur Asrofi; Nova Rhyesa Gita Harianja (Journal of International Conference Proceedings, 2022)
This study aims to identify organic products that have sustainability prospects for the MSMEs of organic product in Malang Raya during Covid-19 outbreak. The analytical method used is descriptive based on quantitative and qualitative data. The object of research is MSME of organic products in Malang Raya. The basic concept used is the sustainability livelihood approach (SLA). The SLA concept examines various assets (pentagon assets), which include aspects of capital: human, social, physical, environmental and financial. Based on the results of the identification of the MSMEs, organic products that are successful are organic agricultural products to meet the needs of healthy food (food safety). The results of the market survey during the Covid-19 pandemic also showed a trend of public interest in consuming organic food, so that there were opportunities for MSMEs of organic products in Malang Raya to seize this opportunity. In this study, it is possible to determine the condition of the assets owned by organic products MSMEs based on the SLA concept. The assets owned by MSMEs can be used to capture these opportunities. Thus, it can be said that behind the Covid-19 outbreak there is a blessing for MSMEs of organic products.Â Keywords: Covid-19 Outbreak, MSME Organic Products, SLA Concept.